Feline Morbillivirus in Southern Italy: Epidemiology, Clinico-Pathological Features and Phylogenetic Analysis in Cats - Giulia Donato; Marisa Masucci; Eliana De Luca; Angela Alibrandi; Massimo De Majo; Shadia Berjaoui; Camillo Martino; Cyndi Mangano; Alessio Lorusso; Maria Grazia Pennisi (Viruses, 2021)
Feline morbillivirus (FeMV) was isolated for the first time in 2012 with an association with chronic kidney disease (CKD) suggested. This study aimed at investigating in cats from southern Italy FeMV prevalence and risk factors for exposure to FeMV, including the relationship with CKD; sequencing amplicons and analyzing phylogeny of PCR positive samples. Blood serum, K3EDTA blood and urine samples from 223 cats were investigated. Ten carcasses were also evaluated. FeMV RNA was detected in 2.4% (5/211) blood and 16.1% (36/223) urine samples. One carcass tested positive by qPCRFeMV from kidney, urinary bladder, and submandibular lymph nodes. Antibodies against FeMV were detected in 14.5% (28/193) cats. We followed up 27 cats (13 FeMV positive cats) and documented in some cases urine shedding after up to 360 days. Older and foundling cats and cats living in rescue catteries, were more frequently infected with FeMV. A significant correlation between FeMV and higher serum creatinine values or low urine specific gravity was found. FeMV positivity was significantly associated with retroviral infection, and the presence of some clinical signs apart from CKD clinicopathological markers. Our study highlights the possibility of a link between FeMV exposure and CKD and a general impairment of feline health.